Analysis of total ionizing dose response of optimized fin geometry workfunction modulated SOI-FinFET. (July 2022) - Ray, Abhishek; Naugarhiya, Alok; Mishra, Guru Prasad
Abstract: The total ionizing dose (TID) response of SOI-FinFET with linear gate workfunction modulation is presented and evaluated. The gate metal workfunction is linearly modulated from source to drain to maintain the electrostatic integrity of the device. At the higher radiation dose (2000 krad), the proposed device has shown reduced Off-current by 2-decade leads to improvement in current switching ratio. Moreover, the proposed device offers 9% and 3% improvement in subthreshold swing before and after the radiation, respectively. During irradiation the trap charges are found in the BOX layer and SiO2 /Si interface. These charges contributed towards shifting of threshold voltage (Vth ). The linear workfunction modulation shows a 73% more Vth as compared to single workfunction FinFET for radiation of 2000 krad dose. As per simulation results, the proposed device is reliable and capable to sustain in the radiation environment. Highlights: Total ionizing dose response of SOI-FinFET with linear gate workfunction modulation is studied. The gate metal workfunction is linearly modulated from source to drain to maintain the electrostatic integrity of the device. Fin geometry of the proposed model is optimized to get higher current switching ratio. At the higher radiation dose (2000 krad), the proposed device shows reduced Off-current by 2 decades. The linear workfunction modulation shows a 50% minimal shift in Vth .